1971
DOI: 10.1136/bmj.1.5744.315
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Overnutrition among Artificially Fed Infants in the Sheffield Region

Abstract: SummaryArtificially-fed 6-week-old infants in the Sheffield region are heavier than would be predicted from their birth weights and show a greatly increased incidence of excessive weight gain. These findings are associated with caloric intakes that exceed the classic 50 calories/lb/day (110 calories/kg/day) with a universal tendency to early feeding with cereals and mixed infant foods.The possible harmful implications of the trend to infantile overnutrition are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

1972
1972
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(39 citation statements)
references
References 2 publications
3
35
1
Order By: Relevance
“…32,33 This correlation presumably reflects the ability of breastfed infants to self-regulate their milk consumption to match their energy needs. 34 The results of this study are consistent with previous studies that showed the benefits of breastfeeding in reducing the risk of developing obesity among infants [34][35][36][37] and shed some additional light on the potential mechanisms behind the association. Although the inverse dose-response relation that we found between breastfeeding intensity and excess weight supports the plausible biological roles of breastfeeding against childhood obesity, the association we found between infant-initiated bottle emptying and excess weight suggests that low self-regulation among bottle-fed infants, perhaps as a result of their inability to respond to internal satiety cues, may also explain why breastfeeding protects against childhood obesity.…”
Section: Discussionsupporting
confidence: 90%
“…32,33 This correlation presumably reflects the ability of breastfed infants to self-regulate their milk consumption to match their energy needs. 34 The results of this study are consistent with previous studies that showed the benefits of breastfeeding in reducing the risk of developing obesity among infants [34][35][36][37] and shed some additional light on the potential mechanisms behind the association. Although the inverse dose-response relation that we found between breastfeeding intensity and excess weight supports the plausible biological roles of breastfeeding against childhood obesity, the association we found between infant-initiated bottle emptying and excess weight suggests that low self-regulation among bottle-fed infants, perhaps as a result of their inability to respond to internal satiety cues, may also explain why breastfeeding protects against childhood obesity.…”
Section: Discussionsupporting
confidence: 90%
“…The almost 40-fold difference was attributed to the different fat composition of the proprietary brands of infant formula food on the market in the two countries (23). This finding comes at a time when there is some concern about the overfeeding of infants (5,13,17,19,20) and the quality of manufactured infant foods (2,6). On the question of overfeeding, part of the concern is connected with the uncertainty about the validity of the 'fat cell hypothesis', which suggests that overfeeding in early life leads to an overabundance of fat cells in the body, which in turn might predispose to life-long obesity.…”
Section: It Has Recently Been Reported By Widdowson Et Almentioning
confidence: 88%
“…However, whether or not an infant is breast-fed may have significant effects on neonatal nutrition and growth. Failure to breast feed in early infancy may lead to overnutrition and overweight infants (Taitz, 1971).…”
Section: Anthropometry and Breast Cancermentioning
confidence: 99%